2022
DOI: 10.1111/jcmm.17568
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation‐mediated PI3K‐Art signalling pathway as a therapeutic mechanism in the hydrogen‐induced alleviation of brain injury in septic mice

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Modern studies have shown that there is a link between Th, Scg2, Rpl17, Chl1, Alb and AD [ 15 - 19 ], SPP1, Th, Prex2 play a role in a variety of diseases by regulating the PI3K-AKT signaling pathway [ 20 - 23 ]. In the transcriptome sequencing, the KEGG enrichment analysis of differentially expressed genes was significantly enriched in the PI3K-AKT signaling pathway.…”
Section: Resultsmentioning
confidence: 99%
“…Modern studies have shown that there is a link between Th, Scg2, Rpl17, Chl1, Alb and AD [ 15 - 19 ], SPP1, Th, Prex2 play a role in a variety of diseases by regulating the PI3K-AKT signaling pathway [ 20 - 23 ]. In the transcriptome sequencing, the KEGG enrichment analysis of differentially expressed genes was significantly enriched in the PI3K-AKT signaling pathway.…”
Section: Resultsmentioning
confidence: 99%
“…Further analysis showed changes in protein phosphorylation in the H 2 -treated group, especially in the case of serine, which regulates cell functions. The authors postulated that the PI3K/Akt signaling pathway mediated this process [ 55 ].…”
Section: Hydrogenmentioning
confidence: 99%